Efficacy and Safety of Semicircular Canal Occlusion for Intractable Horizontal Semicircular Benign Paroxysmal Positional Vertigo. (April 2015) - Zhu, Qiubei; Liu, Chang; Lin, Cheng; Chen, Xian; Liu, Tao; Lin, Shunzhang; Fan, Jingping
Background: Some studies have suggested that semicircular canal occlusion is effective and safe for treating intractable posterior semicircular benign paroxysmal positional vertigo (PSC-BPPV), and adverse effects of canal occlusions for intractable horizontal semicircular BPPV (HSC-BPPV) were rarely reported. The aim of this study was to retrospectively discuss the efficacy of semicircular canal occlusion for intractable HSC-BPPV with at least 2 years of follow-up. Methods: From 2000 to 2011, 3 female patients (average age = 60 ± 6.9 years), with a diagnosis of HSC-BPPV refractory to head-shake and barbecue roll maneuver, underwent semicircular canal occlusion treatment in our hospital. The supine roll test was performed to diagnose HSC-BPPV and evaluate the treatment efficacy. Results: All patients with intractable HSC-BPPV had complete resolution of their positional vertigo after semicircular canal occlusion with a negative supine roll test. All patients reported transient postoperative disequilibrium, nausea, and vomiting, which resolved within 2 weeks. In addition, 1 patient (33.3%) had transient tinnitus, which resolved after 4 months. There were no other significant long-term complications. Conclusion: Semicircular canal occlusion appears to be a safe and well-tolerated treatment modality for intractable HSC-BPPV. However, further studies with large sample sizes are needed to confirm our conclusion.